Dynamic presentation boosts the Ebbinghaus illusion but reduces the Müller-Lyer and orientation contrast illusions - Takao, Saki (J Vis, 2021)
Mruczek et al. (2015) showed that a moving version of the Ebbinghaus illusion almost doubles in strength compared to the standard version. In their stimulus, the size of the surrounding inducers was modulated between large and small and the whole stimulus was made to drift during the surround modulation. We first replicated the original dynamic Ebbinghaus illusion and then explored dynamic presentations for other simultaneous contrast and geometric illusions. We found no increase in illusion strength in any that we sampled. Here we report the results for the Müller-Lyer illusion and the orientation contrast illusion. Surprisingly, when these two illusions were presented dynamically, their effects were greatly reduced for the Müller-Lyer illusion and eliminated for the orientation contrast illusion.